Cardiovascular Outcomes in Patients with Normal and Abnormal 24-Hour Ambulatory Blood Pressure Monitoring - P. Iqbal; Louise Stevenson (International Journal of Hypertension)
Introduction. 24-hour ambulatory blood pressure monitoring (ABPM) plays an important role in assessing cardiovascular prognosis, through presence or absence of ABPM-related prognostic features. Objectives. To study relationship between 24-hour ABPM and cardiovascular outcomes in patients from Chesterfield Royal Hospital. Material and Methods. Over 12 months from the 1st of August 2002, 1187 individuals had 24-hour ABPM performed. Cardiovascular outcomes were studied in a subset (297) of the original cohort, made up by every 4th consecutive subject. The following ABPM-related prognostic features were studied—high day time systolic and diastolic BP (≥135, ≥85 mmHg), high night time systolic and diastolic BP (≥120 mmHg, ≥75 mmHg), absence of nocturnal dip (≤10% fall in night time SBP), high early morning SBP (≥140 mmHg), and morning surge (≥20/15 mmHg). The cardiovascular outcomes studied in the fourth table included fatal and nonfatal MI, new diagnosis of angina, acute coronary syndrome, sudden cardiac death, cardiac arrhythmias, acute LVF, cerbrovascular events, peripheral vascular disease, abdominal aortic aneurysm, and CKD stage 3 or above. Results. Over a followup period of 2015±116 days (1720–2305 days) 82 cardiovascular events occurred in 61 subjects. Cardiac arrhythmias were the most common CV outcome (34 events) followed by cerebrovascular events (15). Statistically significant associations found were between cerebrovascular events and absent nocturnal dip ≤ 10% (𝑃=.05) and high day time DBP (𝑃=.029), peripheral vascular disease and morning surge ≥ 20/15 mmHg (𝑃=.014), cardiac arrhythmias and high day time and night time DBP (𝑃=.009 and .033, resp.). Conclusion. Significant associations were found between cerebrovascular events and absent nocturnal dip ≤ 10% and high day time DBP, peripheral vascular disease and morning surge ≥ 20/15 mmHg, cardiac arrhythmias and high day time and night time DBP.